2020
DOI: 10.3855/jidc.11025
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin and vancomycin resistance in coagulase-negative Staphylococci isolated from the nostrils of hospitalized patients

Abstract: Introduction: Nasal colonization by coagulase-negative Staphylococci (CoNS) play an important role in nosocomial infections. This study aims to determine antibiotics susceptibility pattern and molecular screening of methicillin- and vancomycin-resistant nasal CoNS among hospitalized patients. Methodology: Nasal swabs were collected from 202 inpatients at Prince Hamzah Hospital, Jordan. Swabs were processed according to standard microbiological procedures to isolate Staphylococci. Antibiotic susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
4
14
1
2
Order By: Relevance
“…Currently, vancomycin, linezolid and rifampicin are the treatment of choice for Staphylococcus haemolyticus infections 14, 21 , our results showed that resistance to vancomycin and linezolid do not exist, particularly with the absence of vanA gene (0% in this study) which in agreement with what reported worldwide, however, resistance to rifampicin exhibited by 30% of the isolates reported in this study is alarming, emerging Staphylococcus haemolyticus resistant to rifampicin have been reported 7 , Resistance to glycopeptides (vancomycin and teicoplanin) remains rarely detected in Staphylococcus haemolyticus 3, 6, 14, 16, 18 . Despite the total absence of vancomycin/teicoplanin, linezolid resistant isolates and the apparently low prevalence of rifampicin resistance among Staphylococcus haemolyticus reported in this study, wide surveillance of susceptibility patterns of these drugs among Staphylococcus haemolyticus of clinical origin is mandatory, since the development of resistance to these drugs may exist at low levels 17 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Currently, vancomycin, linezolid and rifampicin are the treatment of choice for Staphylococcus haemolyticus infections 14, 21 , our results showed that resistance to vancomycin and linezolid do not exist, particularly with the absence of vanA gene (0% in this study) which in agreement with what reported worldwide, however, resistance to rifampicin exhibited by 30% of the isolates reported in this study is alarming, emerging Staphylococcus haemolyticus resistant to rifampicin have been reported 7 , Resistance to glycopeptides (vancomycin and teicoplanin) remains rarely detected in Staphylococcus haemolyticus 3, 6, 14, 16, 18 . Despite the total absence of vancomycin/teicoplanin, linezolid resistant isolates and the apparently low prevalence of rifampicin resistance among Staphylococcus haemolyticus reported in this study, wide surveillance of susceptibility patterns of these drugs among Staphylococcus haemolyticus of clinical origin is mandatory, since the development of resistance to these drugs may exist at low levels 17 .…”
Section: Resultssupporting
confidence: 88%
“…In this study 90% of the Staphylococcus hameolyticus isolates exhibited multiple resistance (to three and more antimicrobial classes) (P <0.001, x 2 ). Multiple resistant Staphylococcus haemolyticus of clinical origin are increasingly encountered worldwide 3, 6, 8, 14, 15, 16, 18 . We observed that 100% and 95% of the isolates were resistant to benzylpenicillin and oxacillin respectively, this result was also supported by cefoxitin screening, which is widely accepted as a surrogate for the detection methicillin resistance in staphylococci 19 , as well as the detection of mecA gene by PCR in these isolates.…”
Section: Resultsmentioning
confidence: 99%
“…One limitation of this study is the absence of isolation of the Van A/Van B genes by Polymerase Chain Reaction (PCR). However, it was reported that these genes were absent in the VISA and VRSA strains isolated even in the presence of phenotypic resistance to vancomycin (Al-Tamimi et al, 2020). Hence, the presence or absence of the resistant van A/B genes does not necessarily rule out that strains are not VRSA.…”
Section: Discussionmentioning
confidence: 99%
“…Screening for MRSA among hospital staff is an important component of hospital infection control strategy. Similar to MRSA, nasal carriage constitutes a significant and a common reservoir of CoNS, which are associated with an increased risk of nosocomial infections 5 . However, little data is available for CoNS/MRCoNS colonization in hospital staff .…”
Section: Introductionmentioning
confidence: 99%